Women’s Empowerment Through Community-Based Non-Formal Education: Evidence from a Family Medicinal Plants Program - Gledlys Ela Taruk Allo; Mustangin Mustangin; Sri Wahyuni; Hepy Tri Winarti (Integrated Science Education Journal, 2026)
Purpose of the study: This study aims to describe a community-based health education model for women through the Family Medicinal Plants (TOGA) program in Bhuana Jaya Village. The program was developed to improve women’s knowledge, skills, and awareness in utilizing medicinal plants as an alternative health resource, while promoting family health and strengthening community self-reliance through active participation and empowerment activities. Methodology: This study employed a qualitative research approach conducted in Bhuana Jaya Village, Tenggarong Seberang District, Kutai Kartanegara Regency. Data were collected through observation, interviews, and document analysis. Informants included the head of the dasawisma group, the village head, the neighborhood head, and community members involved in the TOGA program. Data analysis followed the Miles and Huberman model, while data validity was ensured through source and technique triangulation. Main Findings: The findings show that the TOGA program was implemented through planning, implementation, and evaluation stages. Program activities included needs identification, training, counseling, mentoring, and monitoring. The program successfully increased women’s knowledge and skills in cultivating and utilizing medicinal plants, strengthened community participation, enhanced empowerment, and encouraged family independence in maintaining health through the use of TOGA. Novelty/Originality of this study: This study contributes to the development of community-based health education by presenting a practical model that integrates women’s empowerment, local resources, and family health promotion through the TOGA program. The study highlights how dasawisma-based participation can strengthen community engagement and support sustainable health education practices, thereby enriching knowledge on community empowerment and health self-reliance at the village level.